Evolution of the Upper Ocean Stratification in the Japan Sea Since the Last Glacial. Issue 16 (16th August 2020) - Wu, Yonghua; Shi, Xuefa; Gong, Xun; Jian, Zhimin; Zou, Jianjun; Liu, Yanguang; Lohmann, Gerrit; Gorbarenko, Sergey A.; Tiedemann, Ralf; Lembke‐Jene, Lester
Abstract: Paleoceanographic evidence commonly indicates that Last Glacial Maximum surface temperatures in the Japan Sea were comparable to modern conditions, in striking difference to colder neighboring regions. Here, based on a core from the central Japan Sea, our results show similar U K′ 37 ‐ and TEX L 86 ‐derived temperatures between 24.7 and 16.3 ka BP, followed by an abrupt divergence at ~16.3 ka BP and a weakening of divergence after ~8.7 ka BP. We attribute this process to a highly stratified glacial upper ocean controlled by the East Asian Summer Monsoon, increasing thermal gradient between surface and subsurface layers during the deglaciation and the intrusion of Tsushima Warm Current since the mid‐Holocene, respectively. Therefore, we suggest that threshold‐like changes in upper‐ocean temperatures linked to sea level rise and monsoon dynamics, rather than just sea surface temperatures, play a critical role in shaping the thermal and ventilation history of this NW Pacific marginal sea. Plain Language Summary: Abnormally warm surface ocean conditions in the Japan Sea during last glacial are a mystery in Pacific paleoenvironmental history. We analyzed records of U K′ 37 ‐ and TEX L 86 ‐derived temperatures from the central Japan Sea, which suggests an oceanographic evolution from a highly stratified glacial upper ocean, to a deglacial surface‐subsurface thermal gradient control, and subsequently to modern well‐ventilated conditions since the intrusion of the Tsushima Warm Current started after the mid‐Holocene. Our results suggest a combination of critical factors of oceanographic change, rather than a stand‐alone thermal feature, in changing the history in the Japan Sea. Key Points: Alkenone and TEX86 temperatures represent summer SST during the last glacial with low sea level (<−90 m) Isoprenoidal GDGT community structure index indicates a stratified upper ocean during glacial time Increasing tetraether lipid‐based temperature indicates strengthening of the Tsushima Warm Current in the central Japan Sea in the Holocene